Are sectoral stock prices useful for predicting euro area GDP? - Magnus Andersson; Antonello D'Agostino (European Central Bank (ECB), 2008)
This paper evaluates how well sectoral stock prices forecast future economic activity compared to traditional predictors such as the term spread, dividend yield, exchange rates and money growth. The study is applied to euro area financial asset prices and real economic growth, covering the period 1973 to 2006. The paper finds that the term spread is the best predictor of future growth in the period leading up to the introduction of Monetary Union. After 1999, however, sectoral stock prices in general provide more accurate forecasts than traditional asset price measures across all forecast horizons.
Keywords: C52; C53; 330; asset prices; forecasting models; Börsenkurs; Wirtschaftswachstum; Prognoseverfahren; Theorie; EU-Staaten